Why the stars did not align understanding citizens' negotiation of their politics as fans of kakampink celebrities during the 2022 Philippine elections - Giron, Alyssandra Marian A.
Celebrities’ star power has long been utilized in politics to sway voters, especially their fans. But the 2022 election results challenge this norm, as Leni Robredo and Kiko Pangilinan failed to win despite endorsement by many prominent local celebrities. Consequently, this study seeks to understand how citizens negotiate their politics as fans of celebrities with political endorsements. Thirteen (13) one-on-one, semi-structured interviews, along with drawing and ranking activities, were conducted. Results were analyzed and interpreted using Francesco Alberoni's "The Powerless Elite" and Herbert Menzel and Elihu Katz's "Multi-Step Flow of Communication" theories. Findings revealed that being fans of their favorite celebrities does not necessarily translate into economic and political support. While political endorsements may interest them, most citizen-fans said that they would still research and evaluate candidates independently. Additionally, celebrities are not among most citizen-fans' top three political opinion leaders. Hence. citizen-fans have agency, knowing when to compromise their support for their favorite celebrities and what to prioritize during crucial decision-making moments.